2021
DOI: 10.20473/ccj.v2i1.2021.41-49
|View full text |Cite
|
Sign up to set email alerts
|

Aorto Femoral Bypass Graft in Chronic Limb Ischemia Patient

Abstract: A 44-year-old man was admitted to hospital to be performed re-thrombectomy after previously performed thrombectomy at the referring hospital but did not show clinical improvement. CT angiography results before re-thrombectomy showed a central thrombus measuring 1.1 cm in diameter, and an impression of 2.6 cm long at the branching of the right external Iliaca artery which caused total obstruction of the right illiaca external artery to the distal. Aortofemoral bypass graft surgery is a procedure utilized common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…CLI is characterized as a progressive claudication that may develop into nocturnal rest discomfort and can cause tissue loss in the form of ulcers or gangrene (27,28). The clinical presentation of CLI depends on the degree of ischemia, the presence of an infection, which can exacerbate pain even in the absence of severe ischemia, and concomitant neuropathy that can cause tissue injury or hide pain due to the ulcer process (29). Many of the CLI findings in this study may be attributed by patients who only recently reported their complaints that had been prevalent for 6 months to a year earlier.…”
Section: Discussionmentioning
confidence: 77%
“…CLI is characterized as a progressive claudication that may develop into nocturnal rest discomfort and can cause tissue loss in the form of ulcers or gangrene (27,28). The clinical presentation of CLI depends on the degree of ischemia, the presence of an infection, which can exacerbate pain even in the absence of severe ischemia, and concomitant neuropathy that can cause tissue injury or hide pain due to the ulcer process (29). Many of the CLI findings in this study may be attributed by patients who only recently reported their complaints that had been prevalent for 6 months to a year earlier.…”
Section: Discussionmentioning
confidence: 77%
“…2 ALI is the part of peripheral artery disease (PAD) -a blood vessel disorder characterized by progressive narrowing and blockage of blood vessels mainly due to atherosclerosis, ranging from mild plaque formation to chronic vessel occlusion. [3][4][5] Risk factors for PAD include smoking, diabetes mellitus (DM), obesity, high blood pressure, high cholesterol, aging, genetics, heart disease and stroke. [3][4][5] DM is a major risk factor for PAD 6 and associated with other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Risk factors for PAD include smoking, diabetes mellitus (DM), obesity, high blood pressure, high cholesterol, aging, genetics, heart disease and stroke. [3][4][5] DM is a major risk factor for PAD 6 and associated with other diseases. 7,8 Epidemiological data show a strong relationship between PAD and DM with the prevalence of PAD in DM patients is 20%.…”
Section: Introductionmentioning
confidence: 99%